Multiple perspectives on mathematics teaching and learning - Boaler, Jo. (London : Ablex Publishing, 2000)
Multiple Perspectives on Mathematics Teaching and Learning offers a collection of chapters that take a new look at mathematics education.
Includes index.
Keywords: Mathematics -- Study and teaching